2023
DOI: 10.1002/etc.5580
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Drivers of Mercury Bioaccumulation in Fish of a Subarctic Watercourse

Abstract: Mercury (Hg) is a serious concern for aquatic ecosystems because it may biomagnify to harmful concentrations within food webs and consequently end up in humans that eat fish. However, the trophic transfer of mercury through the aquatic food web may be impacted by several factors related to network complexity and the ecology of the species present. The present study addresses the interplay between trophic ecology and mercury contamination in the fish communities of two lakes in a pollution‐impacted subarctic wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…The PCA plot (Figure 6) of fish and metals has indicated that both pike and whitefish (from Russia) have the highest concentrations of mercury; the lowest concentrations are detected in char and trout. High levels of Hg have previously been observed in a study of freshwater fish from the Pasvik watercourse, where the highest levels were measured in the piscivorous fish species, and pike in particular [17]. In berries, mushrooms, and game, the concentrations of mercury were below levels of concern.…”
Section: Common Trends and Possible Reference Indicators Of Pollutionmentioning
confidence: 84%
“…The PCA plot (Figure 6) of fish and metals has indicated that both pike and whitefish (from Russia) have the highest concentrations of mercury; the lowest concentrations are detected in char and trout. High levels of Hg have previously been observed in a study of freshwater fish from the Pasvik watercourse, where the highest levels were measured in the piscivorous fish species, and pike in particular [17]. In berries, mushrooms, and game, the concentrations of mercury were below levels of concern.…”
Section: Common Trends and Possible Reference Indicators Of Pollutionmentioning
confidence: 84%
“…La Colla et al [14] reiterated the significant health risk of THg accumulation in fish muscles along an anthropogenically impacted southeast Argentina's Bahía Blanca estuarine ecosystem. Aquatic MeHg concentrations and biomagnification above acceptable limits in fish communities (732-918 ng/g), frogs (1.075 ng/g), and riparian spiders (347-1140 ng/g) in tropical highland aquatic systems in southwest Colombia have also been reported [18][19][20]. In addition, Lino et al [21] observed that artisanal and small-scale gold mining (ASGM) and deforestation were the primary sources of THg and MeHg in Brazil's Tapajós River basin.…”
Section: Introductionmentioning
confidence: 95%